2016
DOI: 10.1002/2015gb005289
|View full text |Cite
|
Sign up to set email alerts
|

How well do global ocean biogeochemistry models simulate dissolved iron distributions?

Abstract: Numerical models of ocean biogeochemistry are relied upon to make projections about the impact of climate change on marine resources and test hypotheses regarding the drivers of past changes in climate and ecosystems. In large areas of the ocean, iron availability regulates the functioning of marine ecosystems and hence the ocean carbon cycle. Accordingly, our ability to quantify the drivers and impacts of fluctuations in ocean ecosystems and carbon cycling in space and time relies on first achieving an approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
387
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(441 citation statements)
references
References 97 publications
17
387
1
1
Order By: Relevance
“…It is worth noting that Parekh et al (2006) found ∆DIC dis /∆DIC soft of 2 in response to iron fertilization, using a modern ocean circulation, as analyzed by Ito and Follows (2013). We also caution that the quantitative values of DIC soft and DIC dis resulting from the altered iron flux 5 should be taken with a grain of salt, given the very large uncertainty in models of iron cycling (Tagliabue et al, 2016).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It is worth noting that Parekh et al (2006) found ∆DIC dis /∆DIC soft of 2 in response to iron fertilization, using a modern ocean circulation, as analyzed by Ito and Follows (2013). We also caution that the quantitative values of DIC soft and DIC dis resulting from the altered iron flux 5 should be taken with a grain of salt, given the very large uncertainty in models of iron cycling (Tagliabue et al, 2016).…”
mentioning
confidence: 81%
“…This includes the Modular Ocean Model version 5, a sea ice module, static land and ice sheets, and a module of Biogeochemistry with Light, Iron, Nutrients and Gases (BLINGv1.5) 5 (Galbraith et al, 2010). Unlike BLINGv0, BLINGv1.5 allows for variable stoichiometry and calculates the mass balance of phytoplankton in order to prevent unrealistic bloom magnitudes at high latitudes, reducing the magnitude of disequilibrium O 2 , which was very high in BLINGv0 (Duteil et al, 2013;Tagliabue et al, 2016).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Because trace metals are necessary for many cellular functions and their abundance or scarcity can influence the BCP, it is important to quantify the surface export of these elements and understand the drivers of trace metal cycling in the upper ocean. Efforts to include metals in global biogeochemical models have illustrated our lack of understanding of the controls on trace metal distributions in the global ocean (Tagliabue et al, 2016;van Hulten et al, 2017) and the surface export estimates contained within Chapter 3 are a first step to improving these models.…”
Section: This Thesismentioning
confidence: 99%
“…Operationally defined solubility of aerosol-derived iron spans approximately two orders of magnitude [87]. This large range, and the uncertainty about the environmental factors that regulate it, presents a challenge to the successful modelling of iron supply to marine ecosystems [9] even if dust deposition can be established reliably.…”
Section: (B) Dissolved Trace Metals In the Upper Water Columnmentioning
confidence: 99%
“…Ocean productivity, in turn, is a major component of the global carbon cycle [8], so there is a recognized need to include dust supply in global biogeochemical models [9].…”
Section: Introductionmentioning
confidence: 99%